Pengaruh Paritas Dan Hemoglobin Terhadap Kejadian Preeklamsia - restiana, Riza; Ernawati, Ernawati; Atika, Atika (Care : Jurnal Ilmiah Ilmu Kesehatan, 2023)
Preeclampsia is one of the leading causes of maternal morbidity and mortality in the world. Parity factors and hemoglobin are suspected of increasing the incidence of preeclampsia. This study aims to determine the effect of parity and hemoglobin on the incidence of preeclampsia. This research is an observational analytic study with a prospective design. The population in this study were preeclampsia pregnant women and healthy pregnant women at Aghisna Medika Kroya General Hospital and Cilacap Regional General Hospital in August–November 2021, with the following inclusion criteria: gestational age 20 weeks, single pregnancy, willingness to become research subjects, and having gadgets. Exclusion criteria were pregnant women who had incomplete medical record data. A total of 36 respondents in the case group were taken by total sampling technique, and 36 respondents in the control group were taken by purposive random sampling technique with a ratio of 1:1. Statistical test using Chi-Square The results showed that 63.89% (23 people) in the case group and 58.33% (21 people) in the control group were multiparas (p = 0.326 0.05), while 69.45% (25 people) in the case group and 58.33% (21) in the control group had normal hemoglobin levels (p = 0.326 0.05). These data show that there is no effect of parity or hemoglobin level on the incidence of preeclampsia.